1995
DOI: 10.1016/0042-6989(95)00061-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two spatially distinct primers and attribute priming on motion induction

Abstract: In a series of experiments, we demonstrate the effects of two spatially distinct primers on motion induction (MI) and the influence of attribute characteristics on the resulting collision site. MI means that a primer such as a spot produces a motion sensation in a subsequently presented geometrical pattern such as a line or a rectangle. This pattern will appear to grow out of the spot. In the present paper we report that when two different locations of the visual field are activated simultaneously by presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 4 publications
1
57
0
Order By: Relevance
“…It has also been suggested that attention could be the general underlying factor, which causes the increase in processing speed (Hikosaka et a1 1993a). In the case of double motion induction (split priming), a split of attention must be assumed or a shift of attention from the first to the second stimulus (Faubert and von Grunau 1995). With the present experiments, however, we cannot discriminate between these possibilities, nor can we resolve the questions of where the effect is produced (early vs late) or whether it is mainly bottom -up or top -down.…”
Section: Is Attention Involved In Motion Induction?mentioning
confidence: 46%
See 3 more Smart Citations
“…It has also been suggested that attention could be the general underlying factor, which causes the increase in processing speed (Hikosaka et a1 1993a). In the case of double motion induction (split priming), a split of attention must be assumed or a shift of attention from the first to the second stimulus (Faubert and von Grunau 1995). With the present experiments, however, we cannot discriminate between these possibilities, nor can we resolve the questions of where the effect is produced (early vs late) or whether it is mainly bottom -up or top -down.…”
Section: Is Attention Involved In Motion Induction?mentioning
confidence: 46%
“…This might indicate the percept of collision near the middle of the bar (perhaps somewhat closer to the first spot), since observers were forced to choose only one direction on every trial. It could also indicate that no motion was perceived within the bar, but previous research has shown unequivocally that a (more o r less) central collision is perceived in this case (von Grunau et a1 1994b;Faubert and von Grunau 1995). As stimulus delay increased, the proportion of responses for motion away from the second spot increased and then remained steady.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Independent modules should be able to fully compute their particular processes on their own. Much perceptual data argue against the existence of independent modules, however, because strong interactions are known to occur between perceptual qualities [2][3][4][5][6] . For example, changes in perceived form or color can cause changes in perceived motion, and conversely; and changes in perceived brightness can cause changes in perceived depth, and conversely.…”
mentioning
confidence: 99%